2012
DOI: 10.1080/02642069.2010.545885
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of experience-oriented customer needs based on the Kano model: an empirical study

Abstract: Based on the concept of experience economy, this study starts off by proposing that goods, services, and experiences are dimensions of experience-oriented service functions, illustrating an integrated approach which adopts the basic Kano model and customer satisfaction coefficients matrix to categorize and prioritize experience-oriented service functions. An empirical study was then conducted to explore customer need attributes for digital television (DTV) applications. As a result, 445 samples in Taiwan are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…, 2012). As Ko et al . (2012) noted, customers consider issues and defects differently when they truly experience them compared to hypothetical scenarios.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…, 2012). As Ko et al . (2012) noted, customers consider issues and defects differently when they truly experience them compared to hypothetical scenarios.…”
Section: Introductionmentioning
confidence: 79%
“…’ s methodology (1996). Customers consider issues differently when they truly experience those (Ko et al. , 2012).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…For example, among previous studies we can mention Garibay et al (2011), which, integrating the Kano model in QFD in the digital library section, collected customers voices, identified customers important needs, and then using this information in QFD, better understanding from the customers' needs were obtained. It is necessary for organizations to identify the important functions from customer's needs and perspectives and deliver the differently perceived values to different customers (Ko et al, 2011). Hence, some researchers (Lin and Pekkarinen, 2011;Matzler et al, 2002;Wang and Ji, 2010) propose the Kano model to categorize the product/service functions and maximize customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Experienced users of a feature, for example, are likely to have different psychological and behavioural tendencies towards the feature than new users. For example, Ko et al (2012) investigated the need for different product attributes among experienced and inexperienced users by using the Kano model and the diffusion of innovation model. Their results showed that experienced users are in a different state of the feature life cycle than inexperienced users.…”
Section: Factors Affecting the Life Cycle Of A Featurementioning
confidence: 99%